(3GdBQGA GdJQHhjI YfO GHf GdMGL GdYHOQj (B: s (3OQGSI JMdjdjI fGbOI (B/ s - (3jGSQ QeRj YHOGdbGOQ GdeQSjs; (3fGOjI jhSa LeGd GdOjf (B: s ((3GdbGgQI (B: s (3jGSQ QeRj YHOGdbGOQ GdeQSj (B: s, 2013)
(3GSJgOaJ GdOQGSI eG jdj(B: (31(B. (3GdcTa Yf GdBQGA GdJQHhjI dGHf GdMGL GdYHOQj hPdc ef NdGd eG cJHg aj cJGHg (B((3GdeONd Edj GdTQY GdTQja(B). (32(B. (3GdESgGe aj JCUjd GdJQHjI GdESdGejI Yf WQjb Gdhbha Ydj GdJQGK GdJQHhj dOj abjg heDQN GLJeGYj cGHf GdMGL GdYHOQj(B. (33(B. (3EMjGA GdJQGK GdJQHhj GdYQHj GdESdGej YehkeG hGdJQHhj efg HTcd NGU hJbQjHg ddfGS ef NdGd JhVjM GdESgGeGJ GdJQHhjI GdeJfhYI ddeacQjf GdeSdejf hOhQge aj JfGhd GdbVGjG GdJQHhjI(B. (3efgL GdOQGSI(B: (3GSJNOe GdHGMK GdefgL GdJGQjNj GdefgL GdeSJNOe deYQaI GdCMhGd hGdCMOGK hhUa GdXQha hGdeeGQSGJ GdJj cGfJ bGFeI aj eLJeY eG aj YUQ eNJda Ch GdJj LQJ aj GdeGVj HgOa age NHQGJ GdHTQjI GdeGVjI HWQjbI eYjfI (B. (3ceG GSJNOe GdHGMK CSdhH JMdjd GdeMJhi HGYJHGQg COGI ef COhGJ GdHMK GdefGSHI HgOa EHQGR eG ai GdcJGH ef ehGWf GgJeGe JQHhjI Ohf GddLhA Edi JChjd eG cJHg GdcGJH UQGMI hef Ke JgJe gPg GdOQGSI HJbOje JMdjd fbOj deMJhi cJGH GdeONd dGHf GdMGL GdYHOQi dJMOjO BQGFg GdJQHhjI ajg s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQHhjI (B- (3bSe CUhd GdJQHjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GHf GdMGL GdYHOQjs; (3GdBQGA GdJQHhjIs; (3GdacQ GdJQHhis